Esensi Cinta Kepada Nabi Muhammad Menurut Al-Qur'an, Hadis, dan Pendapat Ulama dalam Kitab Mahfudzot - Debi Maghfiroh; Ainur Rofiq Sofa (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
Love for Prophet Muhammad SAW is one of the fundamental teachings in Islam that every Muslim should possess. The essence of this love is not only seen in the practice of religious teachings but also reflected in a deep understanding of the Qur'an, Hadith, and the opinions of scholars in the Mahfudzot book. In the Qur'an, love for Prophet Muhammad SAW is depicted as a form of high obedience and devotion to Allah, aligned with the command to follow the Prophet’s sunnah. Numerous Hadiths also highlight the importance of loving the Prophet as a manifestation of love for Allah, with various descriptions of the obligation of Muslims to emulate the Prophet’s behavior. The Mahfudzot book, as a compilation of various prayers and dhikr, also contains many teachings about love for Prophet Muhammad SAW. In this book, scholars explain how this love should be actualized in daily life, both in terms of worship and character. Love for Prophet Muhammad SAW, according to the scholars, is a form of the perfection of faith that brings a Muslim closer to Allah.